Motion-Based Gesture Recognition Algorithms for Robot Manipulation. (7th May 2015) - Marasović, Tea; Papić, Vladan; Marasović, Jadranka
The prevailing trend of integrating inertial sensors in consumer electronics devices has inspired research on new forms of human-computer interaction utilizing hand gestures, which may be set-up on mobile devices themselves. At present, motion gesture recognition is intensely studied, with various recognition techniques being employed and tested. This paper provides an in-depth, unbiased comparison of different algorithms used to recognize gestures based primarily on the single 3D accelerometer recordings. The study takes two of the most popular and arguably the best recognition methods currently in use - dynamic time warping and hidden Markov model - and sets them against a relatively novel approach founded on distance metric learning. The three selected algorithms are evaluated in terms of their overall performance, accuracy, training time, execution time and storage efficacy. The optimal algorithm is further implemented in a prototype user application, aimed to serve as an interface for controlling the motion of a toy robot via gestures made with a smartphone.